Towards the evaluation of cybersecurity threats and challenges in higher education institutions in Saudi Arabia - Khan, Muhammad Asif; Almulhim, Abdelrahman Abdelaziz; Alkati, Safiullah Salem (Edelweiss Applied Science and Technology, 2025)
Digital technologies have become an integral part of the higher education domain, and various platforms are available for students, faculty, and staff to interact with each other. The growth of cyberspace has also increased the threats and challenges of cybersecurity in higher education institutions. Cybersecurity criminals target these institutions for personal gain and compromise sensitive data. Most universities, especially in Saudi Arabia, consider their technology infrastructure secure from hackers without understanding the extent of their vulnerability. The current study aims to investigate the issues, threats, and challenges of cybersecurity faced by universities in Saudi Arabia. The assessment of cybersecurity has been evaluated based on the NIST cybersecurity framework, which is the most widely used cybersecurity framework in the industry. The study employed a descriptive research design and a mixed methodology of qualitative and quantitative methods to elicit data from various sources. The findings of the study will help universities strengthen their cybersecurity and address the issues and challenges they are facing. Finally, some recommendations have been provided to assist universities in maintaining data integrity and confidentiality.